IMPLEMENTATION OF VILLAGE AUTONOMY POLICY BASED ON LAW NUMBER 6 OF 2014 - Putri, Anhesa Rinta Deidrayanti; Saputri, Septia Ragil; Manurung, Herlina (Transpublika Publisher, 2023)
Indonesia is a highly diverse country in terms of culture, language, ethnicity, and customs, presenting a challenge in managing the diverse local interests in each region. To address this, the Indonesian government enacted Village Law No. 6 of 2014, granting villages the authority to manage natural resources, human resources, and infrastructure development within their areas. However, the implementation of village autonomy under this law still faces various challenges and obstacles. Insufficient capacity and human resources in villages, coupled with a lack of knowledge and technology, hinder effective decision-making that caters to the needs of the village community. This study aims to analyze the implementation of village autonomy policy based on Law No. 6 of 2014 in Indonesia. Using a qualitative approach with a legal perspective (Statue approach), the researchers examine the relevant laws and regulations pertaining to the legal issues at hand. The study concludes that the pre-Law No. 6 of 2014 implementation of village autonomy was limited and did not fully empower the villages.